Direct C–H Arylation Polymerization to form Anionic Water-Soluble Poly(3,4-ethylenedioxythiophenes) with Higher Yields and Molecular Weights - Ayalew, Hailemichael; Wang, Tian-lin; Wang, Tsai-Hui; Hsu, Hsiu-Fu; Yu, Hsiao-hua (Synlett, 2018)
A facile and environmentally benign Pd-catalyzed direct C–H arylation polymerization (DAP) has been developed for the syntheses of homo- and copolymers of anionic-group-functionalized 3,4-ethylenedioxythiophenes with high yields (up to 99%), high molecular weights, and narrow polydispersities. The effects of various Pd catalysts, phosphine ligands, and additives on the properties of the polymers have been examined. The method gives anionic poly(3,4-ethylenedioxythiophenes) with higher molecular weights than those produced by the previously reported chemical or electrochemical methods. The method was also used to synthesize polymers functionalized with carboxylic acid groups without the need for protection/deprotection steps. The resulting polymers can be processed from water or highly polar organic solvents. We also demonstrated a phosphine-free, water-mediated, Pd-catalyzed DAP. The anionic poly(3,4-ethylenedioxythiophenes) were stable in water, and are promising for applications in sensors, drug delivery, and cell engineering.
Keywords: polyethylenedioxythiophenes; C–H arylation; palladium catalysis; anionic polymers; step-economic syntheses; polymerization